Risk Perception of COVID-19 in Indonesia During the First Stage of the Pandemic - Tejamaya, Mila; Widanarko, Baiduri; Erwandi, Dadan; Putri, Amelia Anggarawati; Sunarno, Stevan D. A. M.; Wirawan, I Made Ady; Kurniawan, Bina; Thamrin, Yahya (Frontiers in Public Health, 2021)
Community perceptions of early-stage pandemics may have significant implications for subsequent disease control and management. Perceptions of COVID-19 among Indonesian citizens were assessed 2 months after the first reported case in the country. The study used an online survey tool, which was adapted from a standardized questionnaire for risk perception of an infectious disease outbreak. The questions of the survey involved respondents' perceived level of knowledge, preparedness, efficacy of control measures, newness, infectiousness, seriousness, motivating and hindering factors, and effectiveness of prevention methods, as well as questions that assessed actual level of knowledge of respondents such as causative agents, modes of transmission, number of total cases, and available control measures. A total of 1,043 respondents participated in this study. The main sources of information of respondents were social media (85.2%) and online news (82.2%). Nearly all respondents were aware that COVID-19 is a viral disease with saliva droplets (97.1%) and contaminated surfaces (86.5%) being its main modes of transmission. Participants showed a good level of knowledge pertaining to control measures, an adequate level of belief toward their efficacy, and a willingness to implement such measures. More than 95% of the respondents perceived COVID-19 to be either serious or very serious. However, the level of anxiety among respondents was moderate, suggesting the presence of risk tolerance in the community. Individual characteristics such as gender, educational background, and occupation were found to have a statistically significant relationship with risk perception and tolerance, but voluntary participation in control measures was high and similar. This indicates that the COVID-19 health campaign during early pandemic in Indonesia was a success. This research also revealed certain areas where health promotion, education, and awareness might be improved.